Study on elemental analysis, pesticides, antioxidant, marker compound and validation of conversion of Ajmodadi Churna, an Ayurvedic formulation into suitable dosage form (Indian Journal of Traditional Knowledge (IJTK), 2023)
With the change in the present scenario of globalization, the importance of standardization of traditional formulation has been more stressed out than before. The major objective of this study was the development of an analytical method for the estimation of some important constituent, pesticides, elemental study of the formulation anti-oxidant activity and to study the effect of conversion of churna to granules of in-house and marketed samples. So, a suitable plan was designed to get comprehensive standardization of this formulation Ajmodadi churna. The paper demonstrates the feasibility of the conversion of Ajmodadi churna in granules form and estimation of piperine: cucalyptol, caryophyllene, and eugenol were done using HPTLC, these constituents have an important role in the activity. Eugenol and Eucalyptol were found more in sample A. Our results demonstrate that Piperine was found more in sample B. A study on pesticide residue was done by the TLC method. None of the samples showed the presence of pesticide in the solvent system. Elements are toxic for the body so its determination is also important for the formulation. The micromeritic properties of prepared granules were also studied. The granules showed better flow property than the powders. Antioxidant activity in different samples was observed. Sample A (in-house formulation) showed better antioxidant activity than sample B (marketed formulation). Superior results are seen from the conducted experiments. Importantly, our results provide evidence for a new approach that could also be useful for the standardization of ayurvedic formulation using modern techniques.